Verification of the DKeff hypothesis along the fatigue crack path in thin and thick Al specimens - Julin Andrs Ortiz Gonzlez; Jaime Tupiass Pinho de Castro; Giancarlo Luis Gomez Gonzles; Marco Antonio Meggiolaro; Jos Luiz de Frana Freire (Fracture and Structural Integrity)
Elber assumed that the actual driving force for fatigue crack growth (FCG) is the effective stress intensity factor ?Keff. To verify this hypothesis, both DC(T) and C(T) specimens are cut from a 6351-T6 Al alloy circular bar with two different thicknesses, 2 and 30mm, tested under fixed ?K and Kmax to simulated plane stress and plane strain FCG conditions. A strain-gage bonded on the back face of the specimens is used to measure the crack length and a custom-made Labview program is used to control the applied load, maintaining ?K and Kmax constant along the crack path. Moreover, the crack opening load is redundantly measured during the FCG tests, using far field strains from the back face gage and near field strains from a series of gages bonded along the crack path, as well as an independent digital image correlation system to measure displacement/strain fields on the face of the specimens. These tests show that the Al specimens reproduce the behavior previously observed in similar tests in 1020 steel: a significant decrease of the opening load as the cracks grow along the specimens, while maintaining a FCG rate essentially constant under the fixed {?K, Kmax} loading, a behavior that cannot be explained by the ?Keff hypothesis.